The Life and works of Jose Rizal - Wani-Obias, Rhodalyn; Aaron Abel Mallari;Janet Reguindin-Estella (South Triangle, Quezon City : C & E Publishing Inc., 2018)
This particular book on Rizal's life and works is a direct product of these efforts to bring Philippine education closer to what is needed and expected in the twenty-first century.
1. Understanding the Rizal Law 2. Nation and Nationalism 3. Remembering Rizal 4. The Life of Jose Rizal 5. The nineteenth Century Philippine Economy, Society and Chinese Mestizos 6. Agrarian disputes 7. Emerging nationalism 8. Imagining nation 9. Noli Me Tangere, Context and content 10. Noli Me Tangere, Continuing relevance 11. Looking at the Filipino Past 12. indolence or Industry 13. El Filibusterismo : Context and Content 14. El Filibusterismo : Continuing relevance 15. The destiny of the Filipino people 16. Biography and national history.
Includes index.
Keywords: RIZAL, JOSE P -- STUDY AND TEACHING